(untitled) (Journal of Face Aesthetics, 2026)
Graves’ orbitopathy (GO) is a chronic autoimmune condition causing inflammation in the orbit, leading to exophthalmos (bulging eyes) and a "startled" look. Untreated, it can cause corneal ulcers or vision loss, making early diagnosis vital. This report details a 37-year-old female admitted for urgent surgery due to progressive GO since December 2023. Presenting with asymmetric exophthalmos, superior orbital muscle enlargement, and excess retrobulbar fat, she was qualified for right orbital decompression surgery. The procedure involved lateral and medial orbital wall access, resection of a bone segment, and removal of 3.5 ml of periorbital fat. This increased orbital volume and successfully reduced the exophthalmos. The patient was also referred for strabismus and eyelid retraction correction, with potential blepharoplasty. Orbital decompression is sometimes an emergency procedure in advanced GO. Treatment is individualised and interdisciplinary, combining drugs, radiotherapy, and surgery based on disease severity.